The Restorative Justice Orientation to Hoax Spreaders on Social Media: Urgency and Formulation - Flora, Henny Saida; Khomaini, Khomaini; Wibowo, Dwi Edi (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The development of the use of digital media has had an impact on the amount of hoax information on social media. The large amount of hoax information in the community has made law enforcement officials immediately apply criminal law enforcement against hoax news spreaders.Purposes of the Research: The urgency and formulation of the application of restorative justice in the crime of spreading hoax information on social media.Methods of the Research: Normative legal research with a concept and statutory approach.Results of the Research: The urgency of implementing RJ for perpetrators of criminal acts of spreading hoaxes on social media because RJ's orientation is to provide compensation for victims as well as having a future orientation to educate the public so they can prevent criminal acts from occurring. The application of RJ in cases of criminal acts of spreading hoaxes on social media can be formulated by regulating the application of RJ in cases of criminal acts of spreading hoaxes on social media by revising the provisions of the SKB UU ITE. Revision of the Joint Decree on the ITE Law by incorporating the RJ aspect as an effort to resolve the criminal act of spreading hoaxes on social media as well as the criminal act of the ITE Law in general.